Germline analysis of an international cohort of pediatric diffuse midline glioma patients - Mateos, Marion; Ajuyah, Pamela; Fuentes-Bolanos, Noemi; El-Kamand, Sam; Barahona, Paulette; Altekoester, Ann-Kristin; Mayoh, Chelsea; Holliday, Holly; Liu, Jie; Cui, Louise; Pfaff, Elke; Mackay, Alan; et al. (Neuro-Oncology, 2025)
Factors that drive the development of diffuse midline gliomas (DMG) are unknown. Our study aimed to determine the prevalence of pathogenic/likely pathogenic (P/LP) germline variants in pediatric patients with DMG.We assembled an international cohort of 252 pediatric patients with DMG, including diffuse intrinsic pontine glioma (n = 153), with germline whole genome or whole exome sequencing.We identified P/LP germline variants in cancer predisposition genes in 7.5% (19/252) of patients. Tumor profiles differed, with the absence of somatic drivers in the PI3K/mTOR pathway in patients with germline P/LP variants versus those without (P = .023). P/LP germline variants were recurrent in homologous recombination (n = 9; BRCA1, BRCA2, PALB2) and Fanconi anemia genes (n = 4). Somatic findings established that the germline variants definitively contributed to tumorigenesis in at least 1% of cases. One patient with recurrent DMG and pathogenic germline variants (BRCA2, FANCE) showed a near-complete radiological response to PARP and immune checkpoint inhibition.Our study determined the prevalence of pathogenic germline variants in pediatric DMG and suggests a role in tumorigenesis for a subset of patients.